2009
DOI: 10.3748/wjg.15.349
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of magnifying endoscopy in post-endoscopic resection scar for early gastric neoplasm: A prospective short-term follow-up endoscopy study

Abstract: AIM:To investigate the relationship between postendoscopic resection (ER) scars on magnifying endoscopy (ME) and the pathological diagnosis in order to validate the clinical significance of ME. From January, 2007 to June, 2008 patients with 129 post-ER scar lesions were enrolled. Mucosal pit patterns on ME were compared with conventional endoscopy (CE) findings and histological results obtained from targeted biopsies. METHODS: RESULTS:CE findings showed nodular scars (53/129), erythematous scars (85/129), and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…They argued that ME-NBI is the most effective method for predicting local recurrences during follow-up endoscopy. 34…”
Section: Usefulness In Evaluation Of the Lesion After Treatmentmentioning
confidence: 99%
“…They argued that ME-NBI is the most effective method for predicting local recurrences during follow-up endoscopy. 34…”
Section: Usefulness In Evaluation Of the Lesion After Treatmentmentioning
confidence: 99%
“…However, less has been reported regarding the correlation of endoscopic findings and pathological findings in post-ER scars, as well as a detailed description of ME-NBI findings in the altered mucosa ( Figure 5 ). In 2009, a prospective short-term follow-up study investigated the relationship between magnifying findings of post-ER scars and the pathological diagnosis [ 43 ]. They found that the presence of nodularity on conventional endoscopy suggested tumor lesions with a sensitivity of 88.9% and a specificity of 62.5%.…”
Section: Me-nbi For Treatment Evaluation and Followupmentioning
confidence: 99%